2016
DOI: 10.1002/sia.6019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanostructured lanthanum fluoborate modified by oleylamine and evaluation of its tribological properties as a lubricating additive in synthetic ester

Abstract: Lanthanum fluoborate modified by oleylamine [denoted as La(BF4)3‐OA] was synthesized as a potential lubricant additive by direct precipitation method with sodium tetrafluoroborate and lanthanum nitrate [La(NO3)3] as the staring materials and oleylamine (OA) as the surface‐modifying agent in distilled water‐ethanol mixed solvent. The effects of reaction temperature, OA to La(NO3)3 ratio, and surfactant cetyltrimethyl ammonium bromide on the size and shape of as‐synthesized La(BF4)3‐OA were investigated. The cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The deconvoluted core-level spectra of C 1s, O 1s, N 1s, S 2p, Mo (3d 5/2 and 3d 3/2 ), Y (3d 5/2 and 3d 3/2 ), and La are depicted in parts b–h of Figure , respectively. Several peaks are observed in the C 1s spectrum (Figure b) at binding energies of 284.7, 285.3, 285.9, 286.8, 287.8, and 289.5 eV, which could be attributed to CC, C–O, C–N, C–S, CO, and −NH–CO bonds of M-rGO. ,,, The spectrum of O 1s (Figure c) exhibits three peaks for M–O bonds of metal oxides [Y–O and La–O], CO, and C–O at 529.7, 530.8, and 531.8 eV, respectively. ,, In the N 1s spectrum (Figure d), two peaks are observable at binding energies of 397.6 and 400.9 eV corresponding to C–NHR and C­(O)–NH–R, respectively, confirming reaction of the −NH 2 group of methionine with the epoxide ring and carboxylic group of GO . The S 2p spectrum (Figure e) displays peaks at 161.2, 162.7, and 164.3 eV according to S 2p 3/2 , S 2p 1/2 , and C–S, respectively. , In the spectrum of molybdenum (Figure f), Mo 3d 5/2 , and Mo 3d 3/2 could be allocated at 228.6 and 231.8 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deconvoluted core-level spectra of C 1s, O 1s, N 1s, S 2p, Mo (3d 5/2 and 3d 3/2 ), Y (3d 5/2 and 3d 3/2 ), and La are depicted in parts b–h of Figure , respectively. Several peaks are observed in the C 1s spectrum (Figure b) at binding energies of 284.7, 285.3, 285.9, 286.8, 287.8, and 289.5 eV, which could be attributed to CC, C–O, C–N, C–S, CO, and −NH–CO bonds of M-rGO. ,,, The spectrum of O 1s (Figure c) exhibits three peaks for M–O bonds of metal oxides [Y–O and La–O], CO, and C–O at 529.7, 530.8, and 531.8 eV, respectively. ,, In the N 1s spectrum (Figure d), two peaks are observable at binding energies of 397.6 and 400.9 eV corresponding to C–NHR and C­(O)–NH–R, respectively, confirming reaction of the −NH 2 group of methionine with the epoxide ring and carboxylic group of GO . The S 2p spectrum (Figure e) displays peaks at 161.2, 162.7, and 164.3 eV according to S 2p 3/2 , S 2p 1/2 , and C–S, respectively. , In the spectrum of molybdenum (Figure f), Mo 3d 5/2 , and Mo 3d 3/2 could be allocated at 228.6 and 231.8 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…8 The spectrum of the ternary nanohybrid exhibits these modes with reduced intensity (Figure S3c). The spectrum of M-rGO, shown as an inset in Figure S3c, exhibits intense peaks at 1347.5 and 1573.4 cm −1 , ascribed to the D 43,57,63 In the N 1s spectrum (Figure 4d), two peaks are observable at binding energies of 397.6 and 400.9 eV corresponding to C− NHR and C(O)−NH−R, respectively, confirming reaction of the −NH 2 group of methionine with the epoxide ring and carboxylic group of GO. 19 The S 2p spectrum (Figure 4e) displays peaks at 161.2, 162.7, and 164.3 eV according to S 2p 3/2 , S 2p 1/2 , and C−S, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Early in 1994, we found that MoS 2 nanoparticles as a lubricant additive can effectively reduce the friction and wear of steel‐steel sliding pair . Since then, various inorganic nanoparticles, including oxide nanoparticles, metal nanoparticles, and other nanostructures have been tested to improve the tribological properties of lubricating oils . Copper is widely used as a solid lubricating material and polymer‐based self‐lubricating filler because of its good ductility, low hardness and shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Some boroncontaining nanoparticles as environmentally friendly inorganic lubricant additives have an enormous application range in comparison with the traditional organic lubricating oil additives since they have excellent tribological properties. [24][25][26][27] Zhao et al 28 reported that the surface functionalized zinc borate incorporated into the liquid paraffin showed superior anti-wear property. In addition, boron nitride nanoparticles as potential lubricating oil additives have attracted considerable attention due to its excellent lubricating properties, superb oxidation resistance, high thermal stability, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%